Treatment of AML Relapse After Allo-HCT - Webster, Jonathan A.; Luznik, Leo; Gojo, Ivana (Frontiers in Oncology, 2021)
With advances in allogeneic hematopoietic stem cell transplant (allo-HCT), disease relapse has replaced transplant-related mortality as the primary cause of treatment failure for patients with acute myeloid leukemia (AML). The efficacy of allo-HCT in AML is a consequence of a graft-versus-leukemia (GVL) effect that is mediated by T lymphocytes, and unique mechanisms of immune evasion underlying post-allo-HCT AML relapses have recently been characterized. Relapsed AML following allo-HCT presents a particularly vexing clinical challenge because transplant-related toxicities, such as graft-versus-host (GVHD) and infections, increase the risk of treatment-related morbidity and mortality. In general, the prognosis of relapsed AML following allo-HCT is poor with most patients failing to achieve a subsequent remission and 2-year survival consistently <15%. The two factors that have been found to predict a better prognosis are a longer duration of post-transplant remission prior to relapse and a lower disease burden at the time of relapse. When considered in combination with a patient’s age; co-morbidities; and performance status, these factors can help to inform the appropriate therapy for the treatment of post-transplant relapse. This review discusses the options for the treatment of post-transplant AML relapse with a focus on the options to achieve a subsequent remission and consolidation with cellular immunotherapy, such as a second transplant or donor lymphocyte infusion (DLI). While intensive reinduction therapy and less intensive approaches with hypomethylating agents have long represented the two primary options for the initial treatment of post-transplant relapse, molecularly targeted therapies and immunotherapy are emerging as potential alternative options to achieve remission. Herein, we highlight response and survival outcomes achieved specifically in the post-transplant setting using each of these approaches and discuss how some therapies may overcome the immunologic mechanisms that have been implicated in post-transplant relapse. As long-term survival in post-transplant relapse necessarily involves consolidation with cellular immunotherapy, we present data on the efficacy and toxicity of both DLI and second allo-HCT including when such therapies are integrated with reinduction. Finally, we provide our general approach to the treatment of post-transplant relapse, integrating both novel therapies and our improved understanding of the mechanisms underlying post-transplant relapse.